There are too many kids with special educational needs - Taberner, Joanne E. (Frontiers in Education, 2023)
Over recent decades, special educational needs (SEN) policy and practice in the UK have been in flux as a succession of governments vacillates with competing social, political and economic agendas. The simultaneous pursuit of educational standards, inclusion and equity has created a fragmented system, as well as cognitive and ethical dilemmas for schools. Moreover, a divisive ‘corporation’ and lucrative SEN industry have been established, contributing to unsustainable growth of the SEN populace and political angst around SEN overidentification. Indeed, the extant literature suggests that for every pupil correctly diagnosed with SEN, another is misdiagnosed, diverting resources from pupils with genuine needs.